Lasting Effects of Low-Frequency Repetitive Transcranial Magnetic Stimulation in Writer’s Cramp: A Case Report - Naro, Antonino; Billeri, Luana; Portaro, Simona; Bramanti, Placido; Calabrò, Rocco Salvatore (Frontiers in Human Neuroscience, 2019)
The treatment of writer’s cramp (W’sC) is essentially based on the use of botulinum toxin. However, additional treatments are sometime required to prolong the effects of the toxin, compensate for its progressive loss of efficacy in some subjects, and re-educate handwriting (e.g., rehabilitation strategies). Low-frequency repetitive transcranial magnetic stimulation (rTMS) has been employed to improve W’sC, but with short-lasting and controversial outcomes. We report on the effects of a long-lasting low-frequency rTMS paradigm on W’sC symptoms. A 25-year-old male with a diagnosis of simple W’sC was enrolled in the study. He underwent an objective assessment using the Writer’s Cramp Rating Scale (WCRS) and the 1-min writing test. Further, we recorded muscle activation of the upper limb during handwriting using an EMG wireless system. The patient was provided with 1,200 biphasic magnetic pulses delivered at 1 Hz over the left premotor cortex (PMC), 15 times scheduled every 2 days, thus covering a period of 5 weeks, followed by 10 days of rest. This block of stimulations was practiced other four times, for a period of 6 months. The patient showed a gradual clinical improvement with the progression of the treatments. W’sC symptoms totally disappeared and all the clinical scores showed a significant improvement after rTMS completion. Such improvement lasted up to 1 year after the end of the treatment. Moreover, we detected a long-lasting improvement in sensorimotor plasticity as measured by a paired associative stimulation protocol. Our case suggests that the long-lasting application of 1 Hz rTMS to PMC is a safe and potentially valuable tool to improve W’sC symptoms enduringly, probably by reverting maladaptive plasticity mechanisms within the sensory-motor areas of the hemisphere contralateral to the dystonic hand.